The London experience - Santos, G (Edward Elgar, 2008)
This chapter discusses the London Congestion Charging Scheme. It provides a thorough and critical discussion of the background, design, effects, and costs and benefits of the scheme, and it indicates its “winners and losers”. Furthermore the chapter elaborates on the possible effects of extending the scheme.